2012
DOI: 10.1155/2012/506571
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Results of Hyperthermic Intraperitoneal Intraoperative Chemotherapy as an Adjuvant in Resectable Pancreatic Cancer

Abstract: Background and Aims. 5-year survival in patients with pancreatic cancer is poor. Surgical resection is the only potentially curative resection. The results of adjuvant treatment either with chemotherapy or with radiotherapy have been contradictory and the incidence of local-regional recurrence remains high. If local-regional recurrence is controlled survival may be expected to increase. Hyperthermic intraoperative intraperitoneal chemotherapy (HIPEC) may be used in order to control local-regional recurrences. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 22 publications
5
32
1
3
Order By: Relevance
“…All patients received crystalloids, colloids, and fresh frozen plasma (mean, 4.8; range, 2-12) during the operation, whereas 27 patients were transfused with red blood cells (mean, 2.8; range, [1][2][3][4][5][6]. No serious intraoperative complications during HIPEC were recorded.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients received crystalloids, colloids, and fresh frozen plasma (mean, 4.8; range, 2-12) during the operation, whereas 27 patients were transfused with red blood cells (mean, 2.8; range, [1][2][3][4][5][6]. No serious intraoperative complications during HIPEC were recorded.…”
Section: Resultsmentioning
confidence: 99%
“…5 Cytoreductive surgery and HIPEC for high-grade malignancy is still debatable, with most surgeons agreeing that the volume of disease and the completeness of cytoreduction are crucial for the overall prognosis. 6 Although the morbidity rate of cytoreductive surgery is acceptable and similar to that associated with other major oncologic procedures, 5 perioperative management of patients during HIPEC remains a challenge for surgeons, anesthesiologists, and intensive care unit physicians. A major issue is the observed hemodynamic instabilities even in low-ASA score patients.…”
mentioning
confidence: 99%
“…Doses of 50-500 mg/m 2 have been advocated for postoperative intraperitoneal chemotherapy and were associated with low toxicity [93][94][95]. Preliminary results demonstrated that HIPEC with 1,000 mg/m 2 for 60 min as adjuvant treatment after curative excision of pancreatic carcinoma is well tolerated [96].…”
Section: Gemcitabinementioning
confidence: 99%
“…Im Jahr 2012 berichteten Tentes et al erstmalig von 21 Patienten, die im Rahmen einer R0-Resektion bei Pankreaskarzinom mit limitierter, resektabler (CC-Score = 0) Peritonealkarzinose eine HIPEC mit Gemcitabin erhielten [62,63]. Bei einer Mortalität von 9,5% und einer Morbidität von 33,3% betrug das mittlere Überleben 11 Monate, bei einem 5-Jahres-Überleben von 23% [62,63].…”
Section: Pankreaskarzinomunclassified
“…Bei einer Mortalität von 9,5% und einer Morbidität von 33,3% betrug das mittlere Überleben 11 Monate, bei einem 5-Jahres-Überleben von 23% [62,63]. Wenngleich diese Werte mit einer systemischen Chemotherapie beim Pankreaskarzinom mit Peritonealkarzinose nicht erreichbar sind, ist die vorgelegte Studie aufgrund ihrer Größe und ihres Designs deutlich limitiert.…”
Section: Pankreaskarzinomunclassified